Robust finite-horizon stability and stabilization for positive switched FM-II model with actuator saturation. (February 2020) - Wang, Jinling; Liang, Jinling
Abstract: In this paper, robust finite-horizon stability and stabilization problems are investigated for a class of Fornasini–Marchesini second (FM-II) type positive switched systems with actuator saturation. Firstly, finite-horizon stability is analyzed for the addressed 2-D model by utilizing the mode-dependent average dwell time method. Secondly, the traditional state feedback control idea is introduced in the system, and sufficient criteria are derived to guarantee the resulting closed-loop system to be positive and finite-horizon stable. Then, an observer-based control scheme is implemented, where the observer is presented to make the system finite-horizon stabilizable. Explicit controller design schemes are also presented for both of these two types of controllers. Finally, two illustrative examples are provided to show effectiveness of the theoretical criteria.